The resistance mechanisms of bacteria against ciprofloxacin and new approaches for enhancing the efficacy of this antibiotic - Shariati, Aref; Arshadi, Maniya; Khosrojerdi, Mohammad Ali; Abedinzadeh, Mostafa; Ganjalishahi, Mahsa; Maleki, Abbas; Heidary, Mohsen; Khoshnood, Saeed (Frontiers in Public Health, 2022)
For around three decades, the fluoroquinolone (FQ) antibiotic ciprofloxacin has been used to treat a range of diseases, including chronic otorrhea, endocarditis, lower respiratory tract, gastrointestinal, skin and soft tissue, and urinary tract infections. Ciprofloxacin's main mode of action is to stop DNA replication by blocking the A subunit of DNA gyrase and having an extra impact on the substances in cell walls. Available in intravenous and oral formulations, ciprofloxacin reaches therapeutic concentrations in the majority of tissues and bodily fluids with a low possibility for side effects. Despite the outstanding qualities of this antibiotic, Salmonella typhi, Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa have all shown an increase in ciprofloxacin resistance over time. The rise of infections that are resistant to ciprofloxacin shows that new pharmacological synergisms and derivatives are required. To this end, ciprofloxacin may be more effective against the biofilm community of microorganisms and multi-drug resistant isolates when combined with a variety of antibacterial agents, such as antibiotics from various classes, nanoparticles, natural products, bacteriophages, and photodynamic therapy. This review focuses on the resistance mechanisms of bacteria against ciprofloxacin and new approaches for enhancing its efficacy.